The impact of economic agglomeration on China’s urban public health - Wu, Honghua; Li, Chen (Frontiers in Public Health, 2024)
City are the core spatial carriers for the development of economic agglomeration and the promotion of national health strategies. While economic agglomeration promotes urban prosperity through economies of scale and agglomeration effects, it may also affect the public health of the agglomeration area. This paper takes 280 cities in China as the research object, and explores the impact of economic agglomeration on public health through a two-way fixed effects model, instrumental variable method, and generalized moment estimation. The results indicate that: (1) the improvement of China's economic agglomeration can significantly promote urban public health, and economic agglomeration is a prerequisite for the improvement of urban public health, but there is no reverse causal relationship. (2) There is regional heterogeneity in the promotion of public health by economic agglomeration. The enhancement of economic agglomeration in Northeast China has the greatest promotion effect on public health, followed by the eastern, western, and central regions; The economic agglomeration enhancement of the pilot medical group in closely connected cities has a greater promoting effect on public health than the pilot medical group in non closely connected cities. (3) Empirical results based on micro sample data show that the improvement of economic agglomeration will also promote the increase of the number of public hospitals in cities.